Analisis Efektivitas Pelayanan Persetujuan Bangunan Gedung di Kota Kupang - Timotius Vincent Nalle; Jacob Wadu; Rouwland Alberto Benyamin; Adriana Rodina Fallo (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine the effectiveness of public services in the issuance of Building Approvals (PBG) in Kupang City. It employs a descriptive qualitative method, focusing on the system approach and goal attainment approach proposed by Stephen P. Robbins. Data were collected through interviews, observation, and documentation at the Kupang City Investment and One-Stop Integrated Service Office (DPMPTSP), the Public Works and Spatial Planning Office (PUPR), and nine informants consisting of technical officials and PBG applicants. The findings reveal that PBG services in Kupang City have not yet operated fully effectively. Although digitalization through SIMBG has improved the submission process and administrative monitoring, the service remains constrained by fragmented systems involving OSS, SI-PINTAR, and manual land technical consideration procedures, the lack of integrated RDTR data, weak inter-agency coordination, and low public digital literacy. Other obstacles include the high cost of licensed architectural services and lengthy processing times that often exceed the 28-working-day standard. Out of 548 applications, only 235 were approved, while 242 remained in the document revision stage. Normatively, most issued permits have complied with the RDTR, yet public compliance remains low, as buildings without PBG are still commonly found and spatial control functions have not been fully optimized. In conclusion, the service has functioned as an administrative instrument for regulating development, but it has not been fully effective as a substantive instrument for fostering public compliance with spatial planning regulations. Greater system integration, harmonization of spatial data, procedural simplification, and stronger public outreach are needed to make the service faster, more reliable, and more inclusive.